Improving English Vocabulary Mastery Through Flashcards Method for Students at SMK Telkom 2 Medan - Simarmata, Maria; Tarigan, Natalia W.P.; M.R, Elvira Rosyida (LPPPI Publishing, 2025)
The purpose of this study is to investigate how well eleventh-grade students at SMK Telkom 2 Medan can master English vocabulary with the use of flashcards. The kids' limited vocabulary, especially in vocational schools where English instruction is frequently limited by time and less engaging techniques, is what spurred the research. Two groups participated in a quantitative study utilizing a quasi-experimental design: the experimental group was taught vocabulary using flashcards, while the control group was instructed using traditional techniques. Multiple-choice vocabulary questions were used in pre-tests and post-tests to gauge students' development. The results showed that whereas the control group's average score only increased from 49.6 to 62.0, the experimental group's improved significantly from 51.6 to 79.2. The flashcard strategy greatly improved students' vocabulary acquisition, according to statistical studies, including paired sample and independent sample t-tests (t-value = 7.24; p < 0.001). Furthermore, the results of the questionnaire showed that the majority of students thought flashcards helped them comprehend word meanings, memorize vocabulary more rapidly, and enjoy studying. To sum up, using flashcards to teach English vocabulary turned out to be a successful and entertaining visual aid. This strategy is appropriate for vocational school settings because it not only improved retention but also raised students' motivation and active participation.